PENGARUH FASILITAS KERJA DAN BEBAN KERJA TERHADAP KINERJA GURU SMP NEGERI 4 KOTA BAUBAU - Ahmad Daholu; Rusdin Rusdin; I Kadek Ariyawan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effect of work facilities and workload on teacher performance at SMP Negeri 4 Baubau City. The research employs a multiple linear regression analysis approach. The population consists of all teachers at SMP Negeri 4 Baubau City, totaling 63 teachers, and a saturated sampling technique was used, in which all population members were included as research samples. Data were collected through observation, questionnaires, and documentation. The results of the study indicate that work facilities have a significant effect on teacher performance, as shown by a t-value of 6.543, which is greater than the t-table value of 1.670, with a significance level of 0.000 (< 0.05). Furthermore, workload also significantly affects teacher performance, with a t-value of 7.026 and a significance level of 0.000. Simultaneously, work facilities and workload have a significant influence on teacher performance, as indicated by an F-value of 50.491, which exceeds the F-table value of 3.15, with a significance level below 0.05. Therefore, it can be concluded that both variables significantly influence teacher performance.